Synthesis and Evaluation of Novel Benzimidazole Conjugates Incorporating Amino Acids and Dipeptide Moieties - Bugday, Nesrin; Kucukbay, F. Zehra; Apohan, Elif; Kucukbay, Hasan; Serindag, Ayfer; Yesilada, Ozfer (Letters in Organic Chemistry, 2017)
Background: Amino acids, short peptide sequences and benzimidazole derivatives play an increasingly important role as therapeutics in areas including antibacterial, antifungal, antiviral, antiinflammatory, antiparasitic, antibiofilm, antidiabetic, and anticancer. Methods: Some novel amino acids and glycine-glycine dipeptide benzimidazole conjugates were synthesized by facile acylation reactions through DCC mediated reactions and their structures were identified by 1H-NMR, 13C-NMR and FT-IR spectroscopic techniques and elemental analysis. In vitro antimicrobial activities of some compounds against Gram positive (Staphylococcus aureus and Enterobacter faceium NJ-1) and Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and yeasts (Candida albicans and Candida tropicalis) were determined by MIC method. Their antioxidant activities were also detected by DPPH method. Results: Sixteen novel benzimidazole conjugates incorporating glycine, alanine, phenylalanine, cysteine and glycine-glycine dipeptide were synthesized and their structures were identified by spectroscopic techniques and elemental analysis. All of the compounds tested showed in vitro antimicrobial and antioxidant activities. Conclusion: Sixteen novel benzimidazole amino acid/dipeptide conjugates were synthesized using DCC mediated one step reaction in moderate yield and high purity, under mild reaction conditions, with full retention of the original chirality. Amino acid or dipeptide substitutions at position 1 of the benzimidazoles were synthesized first time in this work. The results have indicated that the newly synthesized compounds possess low to moderate antimicrobial and antioxidant activities.
Keywords: Amino acid derivatives